2021
DOI: 10.1021/acssuschemeng.0c09139
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Virtual Opioid Bioprofile: A Data-Driven QSAR Modeling Study to Identify New Analgesic Opioids

Abstract: Compared to traditional experimental approaches, computational modeling is a promising strategy to efficiently prioritize new candidates with low cost. In this study, we developed a novel data mining and computational modeling workflow proven to be applicable by screening new analgesic opioids. To this end, a large opioid data set was used as the probe to automatically obtain bioassay data from the PubChem portal. There were 114 PubChem bioassays selected to build quantitative structure−activity relationship (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Indeed, computational models are well established, and successfully/extensively used tools, and especially so for drug development [ 44 ]. They have already been applied to classical and designer benzodiazepines [ 45 , 46 ] and other NPS classes (e.g., synthetic cannabinoids [ 47 , 48 , 49 ], opioids [ 50 , 51 ], hallucinogenic phenylalkylamines [ 52 ], and tryptamines [ 53 ] and phenethylamines [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, computational models are well established, and successfully/extensively used tools, and especially so for drug development [ 44 ]. They have already been applied to classical and designer benzodiazepines [ 45 , 46 ] and other NPS classes (e.g., synthetic cannabinoids [ 47 , 48 , 49 ], opioids [ 50 , 51 ], hallucinogenic phenylalkylamines [ 52 ], and tryptamines [ 53 ] and phenethylamines [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…While eight and two compounds were moderate and strong hTTR binders, respectively. This analysis result indicated that the compounds with no hTTR binding potency or weak binding potency were more easily misclassified than those of moderate and strong hTTR binders, which may be caused by the factor of activity cliffs (i.e., the chemicals with similar structures elicit significantly different activities). , …”
Section: Resultsmentioning
confidence: 97%
“…This analysis result indicated that the compounds with no hTTR binding potency or weak binding potency were more easily misclassified than those of moderate and strong hTTR binders, which may be caused by the factor of activity cliffs (i.e., the chemicals with similar structures elicit significantly different activities). 96,97 Construction of QSAR Models. The optimum kNN-QSAR (Radio) model was developed based on four predictive variables (m), i.e., E HOMO-adj (the chemical form adjusted energies of highest occupied molecular orbital), nArOH, H-052 (H attached to C0(sp3) with 1X attached to next C), and ω adj .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Computational modeling driven by the latest progress of informatics and data science is a promising direction for this goal. In this VSI, Jia et al reported a data-driven modeling study to select safe analgesic drugs . An automatic data-mining tool was used in this study to obtain relevant data from public big data resources to generate predictive models for virtual screening purposes.…”
mentioning
confidence: 99%
“…In this VSI, Jia et al reported a datadriven modeling study to select safe analgesic drugs. 1 An automatic data-mining tool was used in this study to obtain relevant data from public big data resources to generate predictive models for virtual screening purposes. Another study by Minerali et al is to develop a quantitative structure−activity relationship (QSAR) toolbox, named Assay Central, for predicting rat oral acute toxicity of chemicals.…”
mentioning
confidence: 99%